Analisis Keuntungan Usaha Pembuatan Tahu Dan Tempe Pada UD. Pembawa Berkah Di Kota Tomohon Selatan - Mongan, Brando Andri; Rengkung, Leonardus Ricky; Laoh, Esry Olly Harryani (AGRI-SOSIOEKONOMI, 2024)
This study aims to analyze the profit of the tofu and tempeh making business obtained by UD. Pembawa Berkah. The research was conducted from October to December 2023. The research was conducted at the place of business of making tofu and tempeh UD. Pembawa Berkah in South Tomohon City. Data collection methods were carried out by interviewing, recording, and documentation. The data used in this study are primary data obtained directly using interview techniques with the owner of the tofu and tempeh making business. Sampling in this study was done intentionally (purposive sampling). Data analysis used in this study used quantitative analysis, namely, by calculating the difference between revenue and costs used. Data analysis was carried out using descriptive analysis method by presenting the result data in tabular form. The results showed the profit of tofu and tempeh making business at UD. Pembawa Berkah in South Tomohon City, for tofu amounting to IDR4,318,000 and for tempeh amounting to IDR9,181,000. R/C ratio for tofu and tempeh making business at UD. Pembawa Berkah in South Tomohon City, for tofu amounted to 1.25 and for tempeh amounted to 1.34. Based on these results, it shows that the R/C ratio value of the tofu and tempeh business is greater than 1, so that the tofu and tempeh business of UD. Pembawa Berkah in South Tomohon City is profitable and feasible to develop.